2003
DOI: 10.1242/dev.00578
|View full text |Cite
|
Sign up to set email alerts
|

A dual, non-redundant, role for LIF as a regulator of development and STAT3-mediated cell death in mammary gland

Abstract: STAT3 is the key mediator of apoptosis in mammary gland. We demonstrate here that LIF is the physiological activator of STAT3, because in involuting mammary glands of Lif -/-mice, pSTAT3 is absent and the STAT3 target, C/EBPδ, is not upregulated. Similar to Stat3 knockouts, Lif -/-mammary glands exhibit delayed involution, reduced apoptosis and elevated levels of p53. Significantly, Lif -/-glands display precocious development during pregnancy, when pSTAT3 is not normally detected. We show that pERK1/2 is sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
175
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(189 citation statements)
references
References 41 publications
11
175
0
3
Order By: Relevance
“…STAT3 activity was suppressed despite the induction of LIF expression in Nucling-KO glands. Previous studies reported that, LIF activated STAT3 via gp130, which is normally up-regulated after weaning to activate STAT3 (5,6,38). Our results indicated that the loss of Nucling inhibited the gene expression of gp130.…”
Section: Discussionsupporting
confidence: 55%
“…STAT3 activity was suppressed despite the induction of LIF expression in Nucling-KO glands. Previous studies reported that, LIF activated STAT3 via gp130, which is normally up-regulated after weaning to activate STAT3 (5,6,38). Our results indicated that the loss of Nucling inhibited the gene expression of gp130.…”
Section: Discussionsupporting
confidence: 55%
“…LIF and OSM are two IL-6-class inflammatory cytokines that have been shown to control mammary gland remodeling through activation of STAT3 (8,9). These cytokines signal through specific ligand-receptor complexes that share the glycoprotein 130 (gp130) signal transduction subunit, which is essential for STAT3 activation in the involuting gland (41).…”
Section: Jak1mentioning
confidence: 99%
“…Following lactation and the weaning of the young, circulating levels of prolactin (PRL) decline and milk stasis induces the local production of interleukin-6 (IL-6)-class cytokines, in particular, IL-6, leukemia inhibitory factor (LIF), and oncostatin M (OSM). These IL-6-class cytokines trigger a cascade of intracellular events that orchestrate a process known as mammary gland remodeling, which entails the death and selective removal of terminally differentiated alveolar cells (7)(8)(9).…”
mentioning
confidence: 99%
“…interferon-␤ in primary murine pro-B cells (22), and that deletion of Stat3 in mammary gland epithelial cells led to the delay of involution due to the reduction of apoptosis (23) suggest that Stat3 plays a more complicated role in the regulation of cell survival and proliferation. Previously, we generated mutant mice in which Stat3 was ablated specifically in the hematopoietic cell lineage using btie2-cre mice (Stat3 f/f /btie2-cre) (24,25).…”
mentioning
confidence: 99%